The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1001/jamaoncol.2015.5570
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Survival Following Treatment of Metastatic Castrate-Refractory Prostate Cancer With Docetaxel Alone or With Strontium-89, Zoledronic Acid, or Both

Abstract: isrctn.com Identifier: ISRCTN12808747.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 15 publications
4
62
0
Order By: Relevance
“…230 The randomized TRAPEZE trial used a 232 factorial design to compare clinical PFS (pain progression, SREs, or death) as the primary outcome in 757 men with bone metastatic CRPC treated with docetaxel alone or with zoledronic acid, 89Sr, or both. 231 The bone-directed therapies had no statistically significant effect on the primary outcome or on OS in unadjusted analysis. However, adjusted analysis revealed a small effect for 89Sr on clinical PFS (HR, 0.85; 95% CI, 0.73-0.99; P5.03).…”
Section: Agents Related To Bone Health In Crpcmentioning
confidence: 89%
“…230 The randomized TRAPEZE trial used a 232 factorial design to compare clinical PFS (pain progression, SREs, or death) as the primary outcome in 757 men with bone metastatic CRPC treated with docetaxel alone or with zoledronic acid, 89Sr, or both. 231 The bone-directed therapies had no statistically significant effect on the primary outcome or on OS in unadjusted analysis. However, adjusted analysis revealed a small effect for 89Sr on clinical PFS (HR, 0.85; 95% CI, 0.73-0.99; P5.03).…”
Section: Agents Related To Bone Health In Crpcmentioning
confidence: 89%
“…When looking at SSE, two prospective randomised studies in men with mCRPC demonstrated an advantage. The TRAPEZE study showed a significant delay in SSEs when docetaxel was combined with zoledronic acid as compared with docetaxel alone and that the combination was safe, but there was no improvement in OS [128]. Interestingly, the benefit in delaying SSEs was in the same range as what was seen in the pivotal zoledronic acid study when chemotherapy was not in use.…”
mentioning
confidence: 95%
“…The concept of targeting bone and tumour is not novel. Prior studies have examined docetaxel in combination with bone-targeting agents that are not known to prolong survival, namely, strontium-89 and rhenium-188-hydroxyethylidine diphosphonate [14,15]. These studies only used one or two doses of the bone-seeking radiopharmaceutical, rather than as a repetitively dosed regimen integrated with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%